Port Concession: Model Determining the Bibliometric Maps by Using VOSViewer - Sri Rahardjo; Laksmono Putranto; Russ Bona Frazilla (Jurnal Teknik Indonesia, 2026)
Ports play a strategic role in supporting economic growth, trade activities, and regional connectivity, particularly in archipelagic countries such as Indonesia. The development of an effective port management system is essential for reducing logistics costs and improving national competitiveness. Port concession schemes have become an important mechanism in port governance by encouraging private-sector participation while maintaining government control over strategic infrastructure. This study aims to identify development trends, publication patterns, influential authors, institutions, countries, keywords, and research clusters related to port concession studies through bibliometric analysis. The research employed a bibliometric approach using 272 scientific documents published between 1937 and 2021, collected from the Google Scholar database. The collected data were analyzed using Microsoft Excel and visualized through VOSviewer software to identify author, institution, country, keyword, and index mappings. The results indicate that research on port concession has experienced continuous development, with journal articles representing the largest proportion of publications. Pallis AA was identified as the most productive author, Petrobel Egypt as the leading institution, and the United States as the country with the highest number of publications. The keyword analysis revealed five major research clusters related to business, public-private partnerships, port performance, concession agreements, and port governance. In conclusion, bibliometric mapping provides an overview of global port concession research trends and can serve as a reference for future studies by identifying dominant themes, influential contributors, and potential research directions.